2017
DOI: 10.1038/s41598-017-13300-8
|View full text |Cite
|
Sign up to set email alerts
|

The loss of P2X7 receptor expression leads to increase intestinal glucose transit and hepatic steatosis

Abstract: In intestinal epithelial cells (IEC), it was reported that the activation of the P2X7 receptor leads to the internalization of the glucose transporter GLUT2, which is accompanied by a reduction of IEC capacity to transport glucose. In this study, we used P2rx7 −/− mice to decipher P2X7 functions in intestinal glucose transport and to evaluate the impacts on metabolism. Immunohistochemistry analyses revealed the presence of GLUT2 at the apical domain of P2rx7 −/− jejunum enterocytes. Positron emission tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
(84 reference statements)
1
20
1
Order By: Relevance
“…Furthermore, the reduced expression of pro-inflammatory genes and reduced levels of plasma cytokines CCL2 and IL6 in P2rx7 KO vs. WT mice may indicate a role for P2X7 in liver upon nutritional inflammatory stimulus. Surprisingly, a recent study reported dyslipidemia and hepatic steatosis along with increased weight gain in P2rx7 KO mice [54]. In this study, lipogenic pathways were shown to be affected, indicating that P2X7 deficiency may deregulate liver function under severe hepatic pathological conditions.…”
Section: E N T P D 1 ( C D 3 9 ) N T 5 E ( C D 7 3 ) P 2 R X 4 P 2 R contrasting
confidence: 51%
“…Furthermore, the reduced expression of pro-inflammatory genes and reduced levels of plasma cytokines CCL2 and IL6 in P2rx7 KO vs. WT mice may indicate a role for P2X7 in liver upon nutritional inflammatory stimulus. Surprisingly, a recent study reported dyslipidemia and hepatic steatosis along with increased weight gain in P2rx7 KO mice [54]. In this study, lipogenic pathways were shown to be affected, indicating that P2X7 deficiency may deregulate liver function under severe hepatic pathological conditions.…”
Section: E N T P D 1 ( C D 3 9 ) N T 5 E ( C D 7 3 ) P 2 R X 4 P 2 R contrasting
confidence: 51%
“…The P2X7 receptor, with its wide-ranging proposed physiological roles in inflammatory disease, cancer, neurological disorders (Bartlett et al, 2014 ; Roger et al, 2015 ; Pevarello et al, 2017 ) and, most recently, metabolic disease (Arguin et al, 2017 ), has been a focus within the pharmaceutical industry and several potent and selective P2X7 antagonists have been developed (Park and Kim, 2017 ). Many of these were thought to be orthosteric, but painstaking and elegant recent work by Alsopp et al, using structure-function and molecular modeling (Allsopp et al, 2017 ), and by Karasawa and Kawate, using functional assay and crystallization of giant panda P2X7 in complex with a series of P2X7 antagonists (Karasawa and Kawate, 2016 ) has clearly demonstrated that these compounds bind to an allosteric site in the extracellular domain distinct from the ATP binding pocket (Figure 4A ).…”
Section: Modulator Binding In P2x Receptor Crystal Structuresmentioning
confidence: 99%
“…P2X7 null mice (P2X7KO) are hyperglycemic, and show glucose intolerance after chronic exposure to high fat/high sucrose diet [11]. Hyperglycemia and concomitant increase of serum insulin levels supports the idea of possible insulin resistance in P2X7KO mice, in which it was also observed hepatic steatosis and facilitated glucose delivery into the bloodstream [12]. The critical involvement of P2X7 in regulating energy metabolism has been further demonstrated in P2X7KO mice showing G. Giacovazzo and S. Apolloni are equal first authors.…”
Section: Introductionmentioning
confidence: 96%